(untitled) (Journal of Contemporary Philology, 2019)
Тhis paper aims to investigate the language journalists use to present news from a certain perspective and thus create public opinion. More precisely, it offers a critical discourse analysis of Macedonian and American journalistic texts reporting on one and the same political event. The main goal is to compare and contrast the specific language tools (lexical-semantic, pragmatic and stylistic) employed in the journalistic texts with different political affiliation. The analysis reveals that there is interrelatedness between textual form and content. Journalists make a careful selection of persuasive strategies to frame the news and present it from certain, often ‘personal’, perspective. The intentionally and cautiously chosen lexical units, pragmatic markers and rhetorical tropes help journalists manipulate the news and present it in such a way that it supports a specific political cause. In this way, they tend to influence the opinions of the people and indirectly impact the political and social situation in the country.